Development of a popular scientific book on water hyacinth liquid organic fertilizer on cowpea growth - Istiqamah Istiqamah; Muhammad Hazimi (HAFECS PRESS, 2025)
Water hyacinth is an invasive aquatic weed that is very detrimental. Its growth is so fast that it can be detrimental in terms of the water sector, fisheries and accelerate siltation of waters. Water hyacinth contains nutrients such as nitrogen, phosphorus, and potassium that are important for plant growth. Popular scientific books on making organic liquid fertilizer from water hyacinth are very limited so there is a need to develop this book. This research aims to make a popular scientific book with the title “Benefits of Water Hyacinth Liquid Organic Fertilizer on Long Bean Growth” that is valid and can be used by all groups. This research uses Educational Design Research (EDR) with a quantitative approach. EDR includes a preliminary research phase, a product prototype design phase (prototyping phase), and a product assessment phase by experts (assessment phase) but in this study only up to the product prototype design phase (prototyping phase). This research uses Tessmer's formative evaluation which includes self-evaluation and expert review. The validation data were analyzed using Akbar's categories. The validation of the developed BIP showed a validity level of 87.65% (very valid), so that this book is suitable for use as a reference in learning and as a source of information for the general public who are interested in the use of water hyacinth as fertilizer or fertilizer. Abstrak. Eceng gondok merupakan tanaman gulma air invasif yang sangat merugikan. Pertumbuhannya yang sangat cepat sehingga dapat merugikaan dari segi bidang perairan, perikanan dan mempercepat pendangkalan perairan. Eceng gondok mengandung unsur hara seperti nitrogen, fosfor, dan kalium yang penting bagi pertumbuhan tanaman. Buku ilmiah populer mengenai pembuatan pupuk cair organik dari eceng gondok sangat terbatas sehingga perlu adanya pengembangan buku ini. Penelitian ini bertujuan untuk membuat buku ilmiah populer dengan judul “Manfaat Pupuk Organik Cair Eceng Gondok Terhadap Pertumbuhan Kacang Panjang” yang valid dan dapat dimanfaatkan oleh semua kalangan. Penelitian ini menggunakan jenis penelitian Educational Design Research (EDR) dengan pendekatan kuantitatif. EDR meliputi tahap pendahuluan (preliminary research), fase perancangan prototipe produk (prototyping phase), serta fase penilaian produk oleh ahli (assessment phase) namun pada penelitian ini hanya sampai tahap perancangan prototipe produk (prototyping phase). Penelitian ini menggunakan evaluasi formatif Tessmer yang meliputi evaluasi diri (self evaluation) dan uji pakar (expert review). Data hasil validasi dianalisis menggunakan kategori Akbar. Validasi BIP yang dikembangkan menunjukkan tingkat kevalidan sebesar 87,65% (sangat valid), sehingga buku ini layak digunakan sebagai referensi dalam pembelajaran maupun sebagai sumber informasi bagi masyarakat umum yang tertarik dalam pemanfaatan eceng gondok sebagai pupuk organik.